Um diário como corpo simbólico: uma leitura da obra O diário de Frida Kahlo: um auto-retrato íntimo - Maria Márcia Franco Gomes (2011)
This work consists in a reflective reading of the book The Diary of Frida Kahlo: an intimate self-portrait, in search of a better understanding concerning the intertwining of the pictorial and verbal narratives contained in such diary. In order to highlight the making of the diary as the artist´s symbolic body, this dissertation aims to setting up relationships in respect to the artist´s imagery existing in the diary, the memory, the intimate writing and the pictorial narrative. The reason to choose this book is based mainly in Frida Kahlo´s plastic and literary creation which presents itself either as an intimate diary and book of memories or as a notebook of sketches and paintings bearing such features as to allow multiple readings.